PENGARUH JUMLAH PENDUDUK DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI KOTA PADANG - Yosiana Maria Saurei; Lisa Gusretni; Adrian Pratama; Cleonita Inglichia; Arifki Fatur Rahma; Ansofino (STKIP Subang, 2026)
This study aims to analyze the effect of population size and unemployment on the poverty rate in Padang City. The study is motivated by the persistent poverty problem, which is influenced by population growth and the high unemployment rate. This research employs a quantitative approach using secondary data obtained from Statistics Indonesia (BPS) of Padang City and West Sumatra Province. The data were analyzed using multiple linear regression to examine the effects of population size and unemployment on the poverty rate. The results indicate that both population size and unemployment affect the poverty rate in Padang City. Partially, unemployment has a more dominant positive effect on increasing poverty, while the effect of population size depends on socio-economic conditions and the labor market's capacity to absorb the workforce. Simultaneously, both variables explain variations in the poverty rate and provide a basis for local governments to formulate poverty reduction policies through employment expansion, human resource development, and population growth control.